2015
DOI: 10.1371/journal.pone.0144583
|View full text |Cite
|
Sign up to set email alerts
|

Density-Dependent Spacing Behaviour and Activity Budget in Pregnant, Domestic Goats (Capra hircus)

Abstract: Very little is known about the spacing behaviour in social groups of domestic goats (Capra hircus) in the farm environment. In this experiment, we studied interindividual distances, movement patterns and activity budgets in pregnant goats housed at three different densities. Norwegian dairy goats were kept in stable social groups of six animals throughout pregnancy at 1, 2 or 3 m2 per individual and their spacing behaviours (i.e. distance travelled, nearest and furthest neighbour distance) and activity budgets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 59 publications
(99 reference statements)
2
11
0
Order By: Relevance
“…The results showed that there were no significant differences in feeding time. The feeding time is similar to the results of Vas and Andersen (2015), which were 56.4±4.9% (2.52 hours) at the early and 38.0±3.8% (1.71 hours) at late pregnancy. The does in the late condition of pregnancy have a higher feeding time.…”
Section: Behaviorsupporting
confidence: 85%
See 1 more Smart Citation
“…The results showed that there were no significant differences in feeding time. The feeding time is similar to the results of Vas and Andersen (2015), which were 56.4±4.9% (2.52 hours) at the early and 38.0±3.8% (1.71 hours) at late pregnancy. The does in the late condition of pregnancy have a higher feeding time.…”
Section: Behaviorsupporting
confidence: 85%
“…The average of laying in the late pregnant condition is in accordance with the normal range and increased based on the aged of pregnancy. Vas and Andersen (2015), reported the time of laying the early, middle, and late pregnancy period that is 18.9 ± 4.6% or 0.85 hours; 26.6±4.4% or 1.2 hours; and 28.9±3.2% or 1.3 hours from a total observation of 4.5 hours.…”
Section: Behaviormentioning
confidence: 99%
“…Moreover, during gestation when kept in groups, individual spaces are reduced, and agnostic relationships increase, which may compromise animals’ behavior and welfare ( Silanikove, 2000 ). This statement was confirmed by Vas and Andersen (2015) . These author studied inter-individual distances, movement patterns and activity budgets in pregnant goats housed at different densities.…”
Section: Discussionmentioning
confidence: 55%
“…Density-dependent mechanisms are the subject of several studies focusing on different animal species [ 57 60 ]. In epidemiological and ecological modeling, one assumes that survival and recruitment rates in free-ranging dogs are driven by the availability of resources in the environment, a density-dependent mechanism [ 61 ].…”
Section: Discussionmentioning
confidence: 99%